Smart pen for intellectual disabilities / Muhammad Akram Ismail … [et al.] - Ismail, Muhammad Akram; Mohd Yusoff, Iskandar Nasrullah; Mohd Nizar, Luqman Danial; Mohd Fadzil, Muhammad Mustaqim; Siman, Nur Aina Safi; Mohd Ali, Nur Asmah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
This paper introduces a smart pen designed to assist individuals with intellectual disabilities in improving their writing skills. There are people out there who have intellectual disabilities and are having difficulties writing properly. The smart pen's aim is to help those who have difficulties writing. Those who have trouble writing properly can now hopefully do so without needing much help. The smart pen can give real-time monitoring and feedback, which can help them be independent. The potential for the products’ commercialization is quite vast as there are quite a lot of people who have intellectual disabilities.